Exploration of ANKRD27 as an immune-related prognostic factor in pan-cancer and hepatocellular carcinoma - Ningzhe Shen; Congcong Fan; Haosun Ying; Xinmiao Li; Weizhi Zhang; Jinglu Yu; Jianjian Zheng; Yifei Li (Frontiers in Oncology)
IntroductionAnkyrin repeat domain 27 (ANKRD27) has been found to be associated with certain cancers. However, its clinical potential in pan-cancer remains unclear.MethodsPublic datasets (TCGA and GTEx) were applied to analyze ANKRD27 expression in multiple cancer types and its correlations with immune scores, immune checkpoint genes, and immune modulatory genes. We also examined ANKRD27 expression in hepatocellular carcinoma (HCC) patients using TCGA and GSE14520 datasets. The upregulation of ANKRD27 was verified via qRT-PCR in vitro. Based on TCGA-HCC, external, and GSE14520 cohorts, the associations between ANKRD27 expression and survival outcome were explored via the Kaplan-Meier survival curve. The effects of ANKRD27 reduction on HCC cell growth, movement, and invasion were evaluated by CCK-8, Wound healing, and Transwell assays.ResultsANKRD27 exhibited aberrant expression in multiple cancers and was correlated with immune traits, including immune infiltration, immune checkpoint genes, and immune modulatory genes. Elevated expression of ANKRD27 was found in TCGA-HCC and GSE14520 cohorts and was confirmed in HCC cell lines. HCC patients with high ANKRD27 expression had poorer prognosis. In vitro, reducing ANKRD27 decreased the capability of proliferation, migration, and invasion in HCC cells. High ANKRD27 expression was associated with sensitivity to certain drugs.ConclusionANKRD27 displays abnormal levels of expression in different cancer types and is linked to immune status in cancer. Furthermore, ANKRD27 may serve as a prognostic predictor for HCC.